(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2023)
Natural attractions and distinctive geographical settings make the coastal environment a promising opportunity for economic and social development. However, coastal areas are susceptible to environmental change, as the recent event shows that sea level rise has damaged Kelanang Beach. Controlling and minimizing the damage caused by sea level rise in the coastal zone is important for the area’s benefit and long-term survival. Coastal protection strategies are essential to the survival of coastal ecosystems and the communities that rely on them. This study proposes coastal protection strategies in sustainable landscape design for Kelanang Beach, Selangor. The study entails the collection of primary data through site observation, in addition to the collection of secondary data which both compiled in the stage of site inventory, analysis, and map synthesis. The proposed design focuses on three main areas: the Kelanang Beach area, the glamping site area, and the mangrove trail area. The aesthetic value and practicality of these areas are highlighted through the design process including a zoning diagram, functional diagram, spatial diagram, design idea plan, and master plan proposal. Coastal protection strategies suggested in the master plan proposal include the integration of hard and soft strategies such as breakwater, planting buffer, and mangrove replanting. The design emphasized vegetation richness to stabilize the beach embankment and maintain the coastal line in the near future. This master plan idea is one of the landscape planning mechanisms to develop coastal areas while strengthening positive symbiotic relationships between local residents, tourists, and the natural environment.